Founding Myths in Chile and the Persistence of Mapuche Memory: From Exclusion to the Struggle for Territory (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this work we reflect on the foundational myths that supported the creation of the Chilean political community, on the basis of which the uniting and integration of diverse social groups, some of them antagonistic to each other, was sought; we also reflect on the strength of adherence to these myths and their importance as affective foundations that unite different peoples around shared symbolic referents. Likewise, we address the conflict that has historically confronted the Chilean State with the Mapuche people in terms of the collective memories they have faced with respect to the creation of an official historical memory and the persistence of the collective memory of the Mapuche people, which has endured until now in spite of the attempts to subsume it into the margins of the official memory; we also reflect on the fundamental role collective memory plays in the struggle of these indigenous people and on the mythological and historical elements that it comprises, as well as on the influence of the symbolic component of it in the political struggle of the Mapuche people.
Keywords: Political Communities; Foundational myths; Chilean State; Collective Memories; Mapuche People.